Front Cover: Stability Enhancement of Iron‐based Perovskite Catalysts by A‐site Substitution for Oxidative Transposition of α‐Bromostyrene to Phenacyl Bromide (ChemCatChem 18/2022). Issue 18 (25th August 2022) - Shibata, Satomi; Kamata, Keigo; Hara, Michikazu
Abstract : The Front Cover shows bromide migration to afford phenacyl bromide over LaFeO3 perovskite nanoparticles under aerobic conditions without the need for additives and light irradiation. In their Research Article, S. Shibata, K. Kamata and M. Hara explain that the stability of Fe‐containing perovskite oxides is significantly improved by selecting the appropriate A‐site metal cation for the oxidative transformation of α‐bromostyrene. The higher catalytic activity of LaFeO3 than other Fe 3+ /Fe 2+ ‐containing simple oxides is caused by a radical‐type mechanism involving surface adsorbed O2 species over p‐type LaFeO3 . The results show that the iron‐containing perovskite structure plays an important role in their activity. More information can be found in the Research Article by S. Shibata, K. Kamata and M. Hara .